PENGARUH EFIKASI DIRI TERHADAP HASIL BELAJAR PPKn SMK MUHAMMADIYAH 1 TANGERANG SELATAN - Masriah, Imas; Atun, Nur (Academy of Education Journal, 2023)
The research aims to determine the influence of self-efficacy on PPKn learning outcomes of students at SMK Muhammadiyah 1 Ciputat, South Tangerang City. The research method used is quantitative with a correlation approach. The total population is 629 students, the reach population is 217 students, and the sample is 86 students. The research results show: (1) the results of the self-efficacy normality test = 0.068 and Sig. =0.200 > 0.05, and PPKn learning outcomes = 0.092 and Sig.=0.069 > 0.05. Because all Sig. > 0.05, then the sample is normally distributed; (2) based on the Anova table, the Fhit value = 0.762 and Sig Deviation from Linearity = 0.803 > 0.05, so that H0 is accepted and the regression relationship between variables X and Y is linear; (3) based on the calculation of the regression line equation for the influence of X on Y, the contribution of self-efficacy to PPKn learning outcomes is 0.415 or 41.5%. This shows that the contribution of self-efficacy to Civics learning outcomes is 41.5%. So Ha is accepted while Ho is rejected, which means that there is a positive and significant influence of self-efficacy on Civics Learning Outcomes.